Percursos críticos da obra de Carolina Maria de Jesus (2012-2017) : uma poética indomável - Herzog, Adriana de Aquino (2019)
This dissertation aims at studying a group of critical texts about the author of Child of the Dark. In order to achieve this, it considers the digital library of Theses and Dissertations presented and published from 2012 to 2017, available on the Sucupira Plataform, from CAPES, as the main point of the investigation; in order to make a larger critical extent. The main themes are shown, with the intention of presenting the researchers’ view in relation to the work. Moreover, this research correlates the data obtained regarding the historiography and the literary criticism, in order to bring a new perspective about the Carolina Maria de Jesus’s writing, considering aspects that conditioned her literary voice to the sociological reading, which is understood in her production. Taking into account the examination, the criteria that make her work be seen through a literature perspective are demonstrated. Finally, the final considerations are written, accentuating the non-conventional nature of the author’s poetics due to the fact that she does not fit into a traditional parameter of analysis.